2023
DOI: 10.1002/jeq2.20452
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bioavailable arsenic threshold and validation of modeled permissible total arsenic in paddy soil using machine learning

Abstract: Minimizing arsenic intake from food consumption is a key aspect of the public health response in arsenic (As)-contaminated regions. In many of these regions, rice is the predominant staple food. Here, we present a validated maximum allowable concentration of total As in paddy soil and provide the first derivation of a maximum allowable soil concentration for bioavailable As. We have previously used metaanalysis to predict the maximum allowable total As in soil based on decision tree (DT) and logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…This is only possible if the groundwater managers have decision tools to spatially predict the nitrate concentration. On one hand, there is a lot of research going on in the field of modeling nitrate in groundwater bodies, mainly on the basis of geostatistical methods such as kriging (Wriedt et al, 2019), numerical models (Nguyen and Dietrich, 2018), and tree-based models such as the random forest (Breiman, 2001;Knoll et al, 2020;Mandal et al, 2023;Sarkar et al, 2023) and gradient boost regression trees (Friedman, 2002). Breiman (2001) showed that the random forest model gives an opportunity for support to water managers and authorities in developing strategies for measures to reduce nitrate inputs into the groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…This is only possible if the groundwater managers have decision tools to spatially predict the nitrate concentration. On one hand, there is a lot of research going on in the field of modeling nitrate in groundwater bodies, mainly on the basis of geostatistical methods such as kriging (Wriedt et al, 2019), numerical models (Nguyen and Dietrich, 2018), and tree-based models such as the random forest (Breiman, 2001;Knoll et al, 2020;Mandal et al, 2023;Sarkar et al, 2023) and gradient boost regression trees (Friedman, 2002). Breiman (2001) showed that the random forest model gives an opportunity for support to water managers and authorities in developing strategies for measures to reduce nitrate inputs into the groundwater.…”
Section: Introductionmentioning
confidence: 99%